Mutation Test in Korean Patients with Colorectal Carcinomas: A Methodological Comparison between Sanger Sequencing and a Real-Time PCR-Based Assay - Sung Hak Lee; Arthur Minwoo Chung; Ahwon Lee; Woo Jin Oh; Yeong Jin Choi; Youn-Soo Lee; Eun Sun Jung (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background Mutations in the KRAS gene have been identified in approximately 50% of colorectal cancers (CRCs). KRAS mutations are well established biomarkers in anti-epidermal growth factor receptor therapy. Therefore, assessment of KRAS mutations is needed in CRC patients to ensure appropriate treatment. Methods We compared the analytical performance of the cobas test to Sanger sequencing in 264 CRC cases. In addition, discordant specimens were evaluated by 454 pyrosequencing. Results KRAS mutations for codons 12/13 were detected in 43.2% of cases (114/264) by Sanger sequencing. Of 257 evaluable specimens for comparison, KRAS mutations were detected in 112 cases (43.6%) by Sanger sequencing and 118 cases (45.9%) by the cobas test. Concordance between the cobas test and Sanger sequencing for each lot was 93.8% positive percent agreement (PPA) and 91.0% negative percent agreement (NPA) for codons 12/13. Results from the cobas test and Sanger sequencing were discordant for 20 cases (7.8%). Twenty discrepant cases were subsequently subjected to 454 pyrosequencing. After comprehensive analysis of the results from combined Sanger sequencing-454 pyrosequencing and the cobas test, PPA was 97.5% and NPA was 100%. Conclusions The cobas test is an accurate and sensitive test for detecting KRAS-activating mutations and has analytical power equivalent to Sanger sequencing. Prescreening using the cobas test with subsequent application of Sanger sequencing is the best strategy for routine detection of KRAS mutations in CRC.